Divorce for Cause: Impacts of the Judicial Process on the Life Project of Individuals. - Chujandama, Clarissa Lleraldine Ruiz; Chumbe, Mayra Sánchez; Bartra, Martin Pinchi (Journal of Posthumanism, 2025)
The implications of the divorce judicial process in the development of the life project of the parties involved were analyzed. It has a case study design with in-depth analysis of specific situations, with a qualitative approach focused on the understanding of the phenomena, using the technique of documentary analysis. The impact of divorce on the development of the life project is addressed and the principle of Iura Novit Curia is analyzed, which allows the judge to apply the law even if the parties do not request it correctly; in the judgments it is observed that the Supreme Court requires conclusive evidence to declare divorce. Divorce not only breaks the legal bond, but also affects the parties emotionally and socially, the judicial process with cause has a significant impact on the life project of the parties, generating not only the dissolution of the marriage bond, but also emotional and social effects.